Pengaruh Skeptisisme Profesional, Independensi dan Komitmen Organisasi Dalam Mendeteksi Fraud Pada Auditor Internal Pemerintah Daerah Provinsi Jambi - DINI ARIDYA PUTRI; Rahayu, Sri; Yudi, Yudi (Magister Ilmu Akuntansi Universitas Jambi, 2024)
This study aims to measure the expertise of government internal auditors in terms of professional skepticism, organizational commitment, and independence. Respondents taken in this study were auditors from the Jambi Provincial Inspectorate, because they are part of the audit entity regulated in the SPKN. The sample in this study was 67 (sixty seven) which was determined based on the certification level of 39 people and the number of PPUPD Functional based on the Certification Level of 28. The data in the study are primary data. The analysis method used is descriptive analysis. The analytical tool used is SPSS 27 and this type of research is quantitative research using survey methods through distributing questionnaires. The results of the study show that professional skepticism affects the auditor's ability to detect fraud. Then independence also has an influence on the auditor's ability to detect fraud, and organizational commitment affects the auditor's ability to detect fraud.